Optimalisasi Literasi Digital Peduli Gaya Hidup Sehat dengan Website Wise Bite - Amru, Roselle Edenia; Pertama, Citra Diah; Sari, Julia Dwi Permata; Latifha, Maryam Ignatia; Ramadani, Ulya Cahya; Safii, Moh (Shaut Al-Maktabah : Jurnal Perpustakaan, Arsip dan Dokumentasi, 2025)
Background of the Study : Low digital literacy and limited public awareness contribute to high food waste in Indonesia, prompting the development of the Wise Bite platform to promote healthy and sustainable food consumption through digital education. Objectives : This study aims to analyze the role of digital literacy in increasing public awareness of food waste management and to examine the Wise Bite platform in helping to change food consumption behavior and reduce food waste. Method : The research method used in the development of the Wise Bite website is a qualitative method with a Design Thinking approach consisting of five stages, namely empathize, define, ideate, prototype, and test. data is collected through observation and informational interviews with potential users to understand the needs and challenges related to healthy lifestyles and food waste. Finding : The results showed that the low level of digital literacy in the community contributed to the high rate of food waste and unhealthy consumption behavior. The trial results show that visual features such as videos, infographics, and quick recipes (lazy cook) are in high demand by users. There are still some challenges and obstacles in developing this website such as limited literacy skills in certain age groups and unstable camera features. Conclusion : The website development process through five stages of design thinking has succeeded in making the Wise Bite website an educational media that presents information related to culinary developments, food processing, and healthy lifestyle tips in an interactive manner.